Nonnatural deaths of children under the age of 5 years in Ontario, Canada: A retrospective autopsy analysis of 10 years (2006-2015) - Syeda Sakina Rizvi; Jayantha C Herath (Wolters Kluwer Medknow Publications, 2017)
The goal of this study is to unravel the common patterns observed among nonnatural deaths of children under 5 years and suggest ways to prevent such unnecessary deaths. The study was confined to the province of Ontario to allow the identification of regional specific patterns. The database at the Office of the Chief Coroner of Ontario was searched for all pediatric deaths from the years 2006-2015. All nonnatural deaths for children under the age of 5 years, including sudden infant death syndrome, were selected for the study. Manner and cause of death along with the corresponding year were recorded in tables. In the 10-year period, 940 nonnatural deaths were identified in Ontario through autopsy records which are equal to approximately 36.7% of the total childhood deaths. There were 295 accidental cases (11.6%) and 71 homicides (2.8%). The leading causes of nonnatural childhood deaths in Ontario were drowning, traffic accidents, blunt trauma, and asphyxia. Nonnatural deaths are preventable through education and training of parents. Implementation of educational interventions can significantly reduce nonnatural deaths of children in Ontario.